A modified sandwich ELISA for accurate measurement of HbF in α-thalassemia carriers containing Hb Bart's and Hb Portland 1. Issue 3 (4th May 2018) - Kerdpoo, Sasiwan; Laopajon, Witida; Kasinrerk, Watchara; Pata, Supansa; Tatu, Thanusak
ABSTRACT: Hemoglobin F (HbF) in blood lysate can be accurately measured by various methods, including immunoassay. In this study, we have produced polyclonal antibody (pAb) against HbF and established a modified sandwich-type ELISA for HbF quantification in blood lysates. The modified sandwich ELISA utilized anti-γ-globin monoclonal antibody clones Thal N/B as the capture antibody (Ab) coated on solid-phase, fluorescein isothiocyanate (FITC)-labeled pAb as the detecting Ab, and HPR-labeled anti-FITC Ab as the signal-generating Ab. By using an optimized blood lysate dilution, the HbF could be measured with no interference from hemoglobin Bart's (Hb Bart's) and hemoglobin Portland (Hb Portland 1) presented in α-thalassemia carriers. HbF levels measured by the modified sandwich ELISA were comparable to those quantified by the standard cation-exchange high performance liquid chromatography. We suggested that this modified sandwich ELISA was able to accurately measure HbF levels even in α-thalassemia carriers containing Hb Bart's and Hb Portland 1 and be an alternative method for HbF measurement.